Apology Strategies Used by Characters in Yes Day Movie - Falentina Jenita Mbeleng; I Made Yogi Marantika (CV Wahana Publikasi, 2023)
The apologies that the characters in the Yes Day movie use are described in this study. Expression of remorse is truly normal in our regular routine since individuals generally commit the errors to one another. The purpose of this study is to learn about and describe apology strategies as well as their functions. The information was assembled from exchanges in the Yes Day film that included expression of remorse. This study gathered nine pieces of information. The narrative-based descriptive qualitative method was used to analyze the data to make it easier for the reader to understand. In the Yes Day movie, the Olshtain Cohen and Rosenstein theory was used to examine the characters’ strategies for apologizing. An Expression of Apology or Illocutionary Force Indicating Device (IFID), an Acknowledgement of Responsibility, an Explanation, an Offer of Repair, and a Promise of Forbearance were all used by the characters in the Yes Day movie, according to the findings of this study. The Illocutionary Force Indicating Device, followed by an Explanation, was the strategy that was used the most frequently based on those strategies. In addition to repairing the relationship between the speaker and the listener, the purpose of the apology strategies was to convey the speaker’s regret for their errors. Also used to maintain a good relationship between two characters, apology.